The Role of HLA Antigens and Steroid Dose on the Course of COVID-19 of Patients After Kidney Transplantation - Dedinská, Ivana; Skálová, Petra; Graňák, Karol; Vnučák, Matej; Baltesová, Tatiana; Žilinská, Zuzana; Jeseňák, Miloš (Frontiers in Medicine, 2021)
Background: Kidney transplant recipients appear to be at higher risk for critical coronavirus disease 2019 (COVID-19). The aim of our analysis was to identify the possible risk factors for a severe course of the COVID-19 disease and to determine the influence of selected human leukocyte antigens (HLA) on the course of the disease. Methods: This is a retrospective, multicentre analysis that included patients with confirmed severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) positivity after kidney transplantation. The group of patients was divided into two subgroups according to the course of the infection, as follows: non-hospitalized and hospitalized. Results: A total of 186 patients (men, 69.4%) with confirmed SARS-CoV-2 positivity were included in the group. The following independent risk factors for the outcome of hospitalization were identified: age at the time of infection (odds ratio [OR] = 1.19, P < 0.0001), body mass index (BMI) more than 29.9 kg/m2 (OR = 7.21, P < 0.0001), prednisone dose/day less than 7.5 mg (OR = 2.29, P = 0.0008), and HLA-DQ2 has protective nature (OR = 0.05, P = 0.0034). Conclusion: Higher doses of corticosteroids (more than 7.5 mg/kg) in standard immunosuppressive regimes and HLA-DQ2 appear to be protective factors in our analysis.